Service provision for diabetes and hypertension at the primary level in the Johannesburg metropolitan area - Smith, Chad Hamilton (My University, 2008)
Executive Summary Non-communicable disease currently accounts for 59% of global deaths and 46% of the global burden of disease. In 2000, 38% of all male deaths and 43% of all female deaths, in South Africa, were due to non-communicable disease. Like all health systems, the South African health system is not adequately equipped to deal with these types of diseases. The burden of chronic disease will grow over time due to factors such as urbanisation and associated behaviours regarding food consumption and physical activity. The World Health Organisation has developed the Innovative Care for Chronic Conditions (ICCC) framework for resource-constrained settings. The ICCC framework is structured into three levels: macro (positive policy environment), meso (community and health care organisation) and micro (health care interactions) levels. Using diabetes and hypertension as examples of chronic disease, this research drew upon portions of this framework to examine service provision for chronic diseases in the Gauteng Province. The overall aim of the study was to document the resources available to manage chronic disease in the Gauteng Province by investigating primary health care clinics, community organisations, and provincial and district support. The objectives were to describe the following: health services offered by primary health care clinics in the city of iv Johannesburg for the management of patients with diabetes and hypertension; the role of district and provincial management in chronic disease care; and the role of community based organisations within the city of Johannesburg in promoting good health, preventing chronic illness, and providing curative and rehabilitative services. The micro level is represented by primary health care (PHC) clinics, the meso level is represented by community-based organisations (CBOs), and the macro level is represented by provincial and regional managers. This is a qualitative, cross-sectional descriptive study. The study population is PHC clinics, associated CBOs, and managers operating in Metropolitan Johannesburg, which is managed by the provincial government. One Gauteng province sub-district was selected by simple random sampling from a list of sub-districts containing at least five provincial PHC clinics. The selected sub-district was located in Soweto and the four PHC clinics and two community health centres were included in the study. Snowball sampling was used to select the CBOs after contacting the PHC clinics. Chronic disease managers at the regional and provincial level were also selected for the study. Data was collected entirely through interviews. One key respondent was selected at each site after contacting the site via telephone. The interview was in-depth and guided by a pre-determined list of questions. The issues probed included topics common to all three levels such as: challenges in chronic disease management, goals for chronic disease management, financial and human resource issues and patient information. Interviews were tape recorded, transcribed and analysed thematically. Ethics approval for the study was obtained from the University of the Witwatersrand’s Human Research Ethics Committee and authorisation to conduct the research was acquired from the Gauteng Provincial Department of Health. A total of 13 people were interviewed. At the micro level (PHC clinics), health care workers believed there was an adequate skill mix for chronic disease care but felt unsupported and understaffed. They did not feel motivated by the incentives currently offered. No health information was maintained at the clinic and all patient information was kept on cards. These cards were used to track patients’ progress, clinic attendance and compliance. The only information collected, and sent for analysis, was a patient headcount. Clinics primarily focused on curative treatment. Patients were deemed to be ‘controlled’ or ‘uncontrolled’ based on their ability to return to the clinic for monthly check-ups and consistently achieve acceptable clinical indicators such as blood pressure and/or blood glucose level. Medical doctors, the only health care workers permitted to initiate insulin therapy, are present only at the community health centres. Patients at PHC clinics must therefore receive referrals and travel to CHC to receive such treatment. PHC sisters did not express an interest in being able to begin insulin therapy, suggesting it is too dangerous and should only be performed by a medical doctor. Five CBO representatives were interviewed. Only two community-based organisations could be identified as having dealt specifically with chronic disease. Both of which focused on diabetes but were inclusive of hypertension due to the number of patients with both conditions. These organisations operated with no budget, paid staff or dedicated office space. They maintained close relationships with clinic staff and ran support groups at the clinic, many times with the help of sisters at the clinic. The other CBOs included in the study were home-based care in nature and dealt primarily with HIV/AIDS. They began treating these chronic disease patients when they realised the stigma of HIV/AIDS was ultimately affecting their outreach. In contrast to the two chronic disease CBOs, the AIDS related organisations all received government training and funding, which included stipends. It was felt that the government training did not provide enough information regarding noncommunicable chronic disease such as hypertension, and instead focused almost exclusively on HIV/AIDS. A monthly meeting was held for all Soweto-based CBOs to discuss issues and receive information from government representatives. There exist dedicated chronic disease programme managers at both regional (covering two districts) and provincial levels. Both levels support one another as they work with the PHC clinics in managing chronic disease. Managers felt free to communicate ‘upwards’ from region to province and province to the national level on an as-needed basis. With respect to PHC services, they saw their role largely as conduits. They provided guidelines to the clinics that were created at the national level and then subsequently monitored their guideline implementation by conducting random site visits. Managers felt that health care worker support was to be accomplished at the clinic level, rather than being their personal responsibility. Chronic disease services, in the study area, held the primarily focus on curative care rather than on health promotion, prevention and early diagnosis through screening. Nearly all patient education was delivered to individuals who had already developed one or more chronic conditions. Community-based organisations motivated those with chronic disease to adhere to treatment protocols, make positive lifestyle choices, and provide patients with a forum to discuss their conditions and learn from one another. They also worked with the government to implement awareness campaigns each month. These campaigns included the community and provided education to those whom had not yet developed a chronic disease. All three levels of the ICCC are functional and communicate with each other, though to varying degrees. While communication between levels is present, there exists a top-down management style where workers feel unsupported. The government is heavily involved in all three levels of chronic disease management. They train and pay PHC clinic staff and CBO workers. The government produces and disseminates all guidelines and protocols and monitor their implementation. The government accomplishes all these tasks while collecting only monthly patient headcounts from each clinic. Patients retain all clinical data and managers see no need to collect any data other than a monthly headcount from each clinic. Nurses are unable to initiate insulin therapy and are unhappy with the current incentive program. There are only two CBOs dedicated to chronic disease, all the rest focus primarily on HIV/AIDS. CBO workers do not feel there is enough training regarding chronic diseases. Each level cite various challenges to successfully managing chronic disease. These include, but are not limited to, low patient compliance, finances, lack of family support, and human resource issues. The research applied only a portion of the ICCC framework to one group of government clinics - provincial PHC clinics and CHCs. Examining a larger number of clinics and managers and applying a greater portion of the ICCC framework would be valuable further research. The following recommendations are a partial list of those generated by this research: • Increase the amount of chronic disease information presented in the mandatory government training of all CBO health care workers. • Construct a comprehensive list of all CBOs that includes: contact information, where they operate, services provided, current client addresses, etc. This will strengthen their ability to partner with one another and reduce overlap in patient care. • Educate patients better regarding how insulin works. This will decrease the usage of herbal medicines that mask health problems and lessen patients’ fear of insulin. • PHC nurses could be trained and permitted to administer and/or initiate insulin therapy. • Enable managers to realise they can affect change in clinic staff, rather than feeling this responsibility belongs solely to the clinic manager.
Keywords: service provision; diabetes; hypertension; Johannesburg